Peningkatan Kapasitas Produksi dan Penjualan Produk Kelapa Gongseng Aceh Pasca Pandemi COVID-19 Melalui Teknologi Tepat Guna dan Pemasaran Digital - Saleh, M; Rasyidin, M; Azmi, Dasril; Shintia, Iin; Miswardi; Rizal, Muhammad (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This article delves into the strategic enhancement of production capacity and sales of Acehnese roasted coconut products in the aftermath of the COVID-19 pandemic, leveraging the application of appropriate technology and digital marketing approaches. The focus of this community engagement initiative lies in addressing the multifaceted challenges faced by the local community, including disruptions in traditional market access and production inefficiencies exacerbated by the pandemic. The objectives of the program are meticulously outlined, detailing the implementation of innovative technological solutions and digital marketing strategies designed to increase production efficiency, product quality, and market reach. The study also discusses the anticipated socio-economic impacts, particularly the potential for sustained community empowerment and economic resilience. The integration of these modern approaches aims to foster long-term sustainability and competitive advantage for micro, small, and medium enterprises (MSMEs) in Aceh, thereby contributing to broader economic recovery and growth.